With Nansen in the North [electronic resource] : a record of the Fram expedition in 1893-96 - Johansen, Hjalmar, 1867-1913.; Braekstad, H. L. (Hans Lien), 1845-1915. (London; New York : Ward, Lock and Co., 1899)
Electronic reproduction. Mode of access: Internet. 44